2003
DOI: 10.1074/jbc.m212930200
|View full text |Cite
|
Sign up to set email alerts
|

Structural Impact of the Leukemia Drug 1-ॆ-d-Arabinofuranosylcytosine (Ara-C) on the Covalent Human Topoisomerase I-DNA Complex

Abstract: 1-␤-D-Arabinofuranosylcytosine (Ara-C) is a potent antineoplastic drug used in the treatment of acute leukemia. Previous biochemical studies indicated the incorporation of Ara-C into DNA reduced the catalytic activity of human topoisomerase I by decreasing the rate of single DNA strand religation by the enzyme by 2-3-fold. We present the 3.1 Å crystal structure of human topoisomerase I in covalent complex with an oligonucleotide containing Ara-C at the ؉1 position of the non-scissile DNA strand. The structure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 41 publications
0
29
0
Order By: Relevance
“…The fact that cytarabine also requires Rad9 to induce S-phase arrest is consistent with earlier reports showing that cytarabine induces replication stress after its incorporation into DNA (66 -69). On the other hand, recent studies have suggested that cytarabine might act like a topoisomerase I poison (37,38). Evidence to support this claim has included (i) the demonstration that the religation step of topoisomerase I is slowed ϳ5-fold when an oligonucleotide containing cytidine arabinoside in place of cytidine at a topoisomerase I cleavage site is exposed to purified enzyme in vitro; (ii) the observation that covalent topoisomerase I-DNA complexes are increased in neoplastic cell lines several hours after the addition of cytarabine to cultures; and (iii) the demonstration that camptothecin-selected P388/camptothecin (CPT) murine lymphoma cells, which lack detectable topoisomerase I and are 4000-fold more resistant to CPT, are 5-fold resistant to cytarabine.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The fact that cytarabine also requires Rad9 to induce S-phase arrest is consistent with earlier reports showing that cytarabine induces replication stress after its incorporation into DNA (66 -69). On the other hand, recent studies have suggested that cytarabine might act like a topoisomerase I poison (37,38). Evidence to support this claim has included (i) the demonstration that the religation step of topoisomerase I is slowed ϳ5-fold when an oligonucleotide containing cytidine arabinoside in place of cytidine at a topoisomerase I cleavage site is exposed to purified enzyme in vitro; (ii) the observation that covalent topoisomerase I-DNA complexes are increased in neoplastic cell lines several hours after the addition of cytarabine to cultures; and (iii) the demonstration that camptothecin-selected P388/camptothecin (CPT) murine lymphoma cells, which lack detectable topoisomerase I and are 4000-fold more resistant to CPT, are 5-fold resistant to cytarabine.…”
Section: Discussionmentioning
confidence: 99%
“…Aliquots derived from equal amounts of protein as assayed by the method of Bradford (46) were separated by SDS-10% PAGE. After polypeptides were transferred to Immobilon-P membranes (Millipore) and subjected to immunoblotting as described (38), bound antibodies were visualized by chemiluminescence (SuperSignal, Pierce).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the exact nature of the damage caused by nucleoside analogs in stalling replication forks is poorly understood, it follows that cellular responses to these agents are likely to overlap those elicited by drugs such as hydroxyurea (HU) that also cause replication forks to stall by limiting dNTP production. Also, crystallographic studies have demonstrated that incorporation of ara-C into DNA causes localized alterations in the DNA duplex (Schweitzer et al, 1994) and stabilizes covalent topoisomerase I-DNA complexes, thus converting the enzyme into a cellular poison (Pourquier et al, 2000;Chrencik et al, 2003). This suggests that cellular responses to nucleoside analogs are also likely to overlap those elicited by the camptothecin family of topoisomerase I active agents.…”
Section: Sensors Of Dna Damage In Replicating Cellsmentioning
confidence: 99%
“…23). The structural distortions induced by incorporation of Ara-C at the ϩ1 position of the complementary nonscissile strand also stabilize the covalent enzyme-DNA intermediate by reducing DNA religation (24). Mutation of conserved residues N-terminal to the active site tyrosine in the yeast and human enzymes also induces Top1p poisoning (12,(25)(26)(27).…”
mentioning
confidence: 99%